Factors influencing the provision of oral hygiene care following stroke: an application of the Theory of Planned Behaviour - Normaliza Binti Ab Malik; Saari Mohamad Yatim; Otto L.T. Lam; Lijian Jin; Colman McGrath (Taylor & Francis Ltd, 2024)
Indexed by Scopus